2021
DOI: 10.3390/fib9070044
|View full text |Cite
|
Sign up to set email alerts
|

Micromechanical Modeling of Anisotropy and Strain Rate Dependence of Short-Fiber-Reinforced Thermoplastics

Abstract: The anisotropy and strain rate dependence of the mechanical response of short-fiber-reinforced thermoplastics was studied using a straightforward micromechanical finite element analysis of representative volume elements (RVEs). RVEs are created based on the fiber orientation tensor, which quantifies the processing-induced fiber orientation distribution. The matrix is described by a strain rate-dependent constitutive model (the Eindhoven glassy polymer (EGP) model), which accurately captures the intrinsic respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…28 Next to this broad experimental validation of the factorizability, it is also validated by employing RVE simulations on SFRTs where a viscoelastic-viscoplastic constitutive model is used to describe the matrix. 29 Inspired by the work of Fara and Pavan, 7 who showed that the modulus, maximum stress, and fracture toughness of SFRTs are directly coupled to fiber orientation in the form of the orientation factor in the main orientation direction, Amiri-Rad et al 30 utilized this observation between the mechanical properties and the fiber orientation, and the factorization with respect to strain rate in a threedimensional (3D) anisotropic viscoelastic-viscoplastic model. Knowing the spatial distribution of fiber orientations and the time-dependent behavior of the matrix, allows the ductile failure of a product to be predicted.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…28 Next to this broad experimental validation of the factorizability, it is also validated by employing RVE simulations on SFRTs where a viscoelastic-viscoplastic constitutive model is used to describe the matrix. 29 Inspired by the work of Fara and Pavan, 7 who showed that the modulus, maximum stress, and fracture toughness of SFRTs are directly coupled to fiber orientation in the form of the orientation factor in the main orientation direction, Amiri-Rad et al 30 utilized this observation between the mechanical properties and the fiber orientation, and the factorization with respect to strain rate in a threedimensional (3D) anisotropic viscoelastic-viscoplastic model. Knowing the spatial distribution of fiber orientations and the time-dependent behavior of the matrix, allows the ductile failure of a product to be predicted.…”
Section: Introductionmentioning
confidence: 99%
“…[58][59][60] RVEs for shortfiber-filled polymers are abundantly used to study the effective composite level elastic properties, that is, Young's modulus, Poisson's ratio, and thermal expansion coefficient with respect to the volume fraction, aspect ratio, and fiber orientation using elastic matrix material models. [61][62][63][64] Strength due to plasticity dominated failure for short-fiber-filled thermoplastic systems and how it is affected by the microstructure was studied using elastoplastic [65][66][67][68] or viscoelastic-viscoplastic 29,69 material models. The elasto-plastic type of constitutive models do not include a proper description of local shear and hydrostatic stress contribution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Breuer et al [20,21] applied the RVE to SFRC including artificial neural networks. Zhang et al investigate the strain rate dependence of SFRC based on RVEs [22] and Jia et al apply the RVE concept to cyclic mechanical and thermal loading [23].…”
Section: Introductionmentioning
confidence: 99%